The use of ketogenic diet in special situations: expanding use in intractable epilepsy and other neurologic disorders - Munhyang Lee (Korean Pediatric Society, 2012)
The ketogenic diet has been widely used and proved to be effective for intractable epilepsy. Although the mechanisms underlying its anti-epileptic effects remain to be proven, there are increasing experimental evidences for its neuroprotective effects along with many researches about expanding use of the diet in other neurologic disorders. The first success was reported in glucose transporter type 1 deficiency syndrome, in which the diet served as an alternative metabolic source. Many neurologic disorders share some of the common pathologic mechanisms such as mitochondrial dysfunction, altered neurotransmitter function and synaptic transmission, or abnormal regulation of reactive oxygen species, and the role of the ketogenic diet has been postulated in these mechanisms. In this article, we introduce an overview about the expanding use and emerging trials of the ketogenic diet in various neurologic disorders excluding intractable epilepsy and provide explanations of the mechanisms in that usage.